2012
DOI: 10.1111/are.12078
|View full text |Cite
|
Sign up to set email alerts
|

Trial grow-out culture of sea cucumberHolothuria scabrain sea cages and pens

Abstract: Field trials were conducted to determine the effects of size, grow-out period and site on the growth and survival of Holothuria scabra. Juveniles were reared in sea cages in two sites for 2 months during two different times of the year. Juveniles from Experiment 1 were subsequently grown in sea pens for 8 months in one site. The significantly lower survival particularly of the small-sized group (<0.1 g) in Pilar is likely due to reduced water and sediment quality because of proximity to fish-farming activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 8 publications
0
10
0
2
Order By: Relevance
“…Sandfish, Holothuria scabra , is the most valuable tropical sea cucumber species that may fetch US$115–640 per kg dry weight (DW) after appropriate processing and up to US$1670 per kg DW for individuals greater than 1.5 kg in weight (Purcell, Hair, et al, ). Given this high value, sandfish has attracted considerable research attention with regard to development of hatchery (Duy, ; Duy, Francis, & Southgate, ; Hair, Kaure, Southgate, & Pickering, ; Militz, Leini, Duy, & Southgate, ), nursery (Gorospe, Altamirano, & Juinio‐Meñez, ; Juinio‐Meñez, Peralta, Dumalan, Edullantes, & Catbagan, ; Sinsona & Juinio‐Meñez, ), and grow‐out production methods (Hair, ; Hair, Mills, McIntyre, & Southgate, ; Hair, Ram, & Southgate, ; Juinio‐Meñez, Evangelio, & Miralao, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sandfish, Holothuria scabra , is the most valuable tropical sea cucumber species that may fetch US$115–640 per kg dry weight (DW) after appropriate processing and up to US$1670 per kg DW for individuals greater than 1.5 kg in weight (Purcell, Hair, et al, ). Given this high value, sandfish has attracted considerable research attention with regard to development of hatchery (Duy, ; Duy, Francis, & Southgate, ; Hair, Kaure, Southgate, & Pickering, ; Militz, Leini, Duy, & Southgate, ), nursery (Gorospe, Altamirano, & Juinio‐Meñez, ; Juinio‐Meñez, Peralta, Dumalan, Edullantes, & Catbagan, ; Sinsona & Juinio‐Meñez, ), and grow‐out production methods (Hair, ; Hair, Mills, McIntyre, & Southgate, ; Hair, Ram, & Southgate, ; Juinio‐Meñez, Evangelio, & Miralao, ).…”
Section: Introductionmentioning
confidence: 99%
“…The optimal stocking densities for A. japonicus in a suspended cage has been determined to be 22.3 ind.m -2 for feed-supplemented pens and 14.1 ind.m -2 for non-feedsupplemented pens (Qin et al 2009). Another sea farming method is sea pen or cage culture, which has been used in H. scabra grow-out (Juinio-Meñez et al 2014;Dumalan et al 2019). Ceccarelli et al (2018) reported that the survival and growth rate of H. scabra was significantly higher at shallow depths with intermediate seagrass cover and high organic carbon content of sediments.…”
Section: Rearing Systems Reliant On Water Qualitymentioning
confidence: 99%
“…Juinio-Menez et al (2012) Tabel 3. Performa pertumbuhan dan sintasan teripang pasir yang diberi pakan percobaan selama empat bulan dalam kantong jaring di tambak 1) .... (Nyoman Adiasmara Giri) melaporkan bobot teripang pasir yang dipelihara dalam karamba jaring apung di laut selama dua bulan hanya mencapai rata-rata 6,0 g dari bobot awal 1-4 g. Teripang pasir yang dipelihara dalam karamba tancap di laut selama lima bulan bobotnya dapat mencapai 164 g dari bobot awal 8-10 g. Namun demikian pertumbuhan teripang yang dipelihara pada karamba jaring tancap ini sangat bervariasi karena pada beberapa unit percobaan juga diperoleh pertumbuhan bobot yang negatif (Juinio-Menez et al, 2012). Pada percobaan budidaya teripang pasir di tambak dengan kepadatan 3 ekor/m 2 dengan ukuran awal 3,8 g dan 23,8 g masing-masing dapat mencapai ukuran 28,0 g dan 60,6 g selama lima minggu pemeliharaan (Lavitra et al, 2009).…”
Section: Analisa Dataunclassified